2006
DOI: 10.1108/09596110610681539
|View full text |Cite
|
Sign up to set email alerts
|

Breaking into emerging international hotel markets

Abstract: Purpose -This paper examines some of the most difficult barriers that hotel chains must overcome when trying to expand internationally. It argues for the importance of the role of well educated hotel management trainees and new graduates in this process. Design/methodology/approach -The methodology was to compare the problems faced by three major international hotel chains (Mövenpick, Kempinski, and Radisson) when expanding into emerging markets with those of a "base case": The Moscow Aerostar Hotel. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Another important contribution of the study is the confirmation that in the international expansion of the hotel business the proactive attitude is relevant, in line with evidence provided by previous research (Hutchinson et al, 2007;Niñerola et al, 2016;Velo and Mittaz, 2006;Pine and Qi, 2004).…”
Section: Theoretical Implicationssupporting
confidence: 85%
See 1 more Smart Citation
“…Another important contribution of the study is the confirmation that in the international expansion of the hotel business the proactive attitude is relevant, in line with evidence provided by previous research (Hutchinson et al, 2007;Niñerola et al, 2016;Velo and Mittaz, 2006;Pine and Qi, 2004).…”
Section: Theoretical Implicationssupporting
confidence: 85%
“…Such a scenario indicates the need to further develop research efforts in the hotel industry sector as to 'why' question, beside 'where' and 'how' options during internationalisation (Niñerola et al, 2016;Velo and Mittaz, 2006;Pine and Qi, 2004). The literature demonstrates that several factors such as firm characteristics and environment do influence the internationalisation decision (Mejri and Umemoto, 2010), but a lack of knowledge exists regarding the factors that drive exporting attitudes (Wood et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Velo and Mittaz (2006), open-mindedness is a crucial attribute if a firm is to develop new organizational forms to be successful in international markets. In their study of the hospitality business, they concluded that open-mindedness was one of the key abilities that helped a firm to find new organizational forms and adapt to a new international environment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In addition, Velo and Mittaz (2006) stated that an employee who are able to address problems faced by customers in an instant will be beneficial on both personal and organizational level. Not much can be expected from a fresh graduate in terms of skills and competency but the their ability to try and apply what they have learn into practice is highly appreciative (Gbadamosi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%